Receptive Human Virtues : A New Reading of Jonathan Edwards's Ethics - Cochran, Elizabeth Agnew, 1977- (Book collections on Project MUSE., 2011)
"An examination of the writings on virtues and ethics of eighteenth-century Puritan Jonathan Edwards"--Provided by publisher